2013
DOI: 10.1007/s13632-012-0056-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Engineered Nickel-Base Alloy Surface Layers Produced by Additive Friction Stir Processing

Abstract: Additive friction stir processing (AFSP) was used as a novel method to create consolidated c 0 -strengthened superalloy surface layers on non-age-hardenable Ni-alloy substrates. A Ni-Cr-Mo superalloy (Haynes Alloy 282) was deposited onto Ni-Cr-Fe alloy (INCONEL TM Alloy 600) plate using a cold-wire gas tungsten arc process and subsequently friction stir processed. Alloy 282 was incorporated into the surface and led to increases in nearsurface hardness to levels over 275 HV 0.3 as-processed. Heat treatment resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The composite prepared via CFAM showed an improvement in bulk density as it reduced the size of pores and hence porosity. Rodelas and Lippold 72 noticed that the advancing side which is more turbulent that the retreating side exhibited higher value of hardness of both higher and lower parametric conditions. A peculiar behaviour was observed on the sample prepared via low heat input parametric combination.…”
Section: Friction Stir Additive Manufacturingmentioning
confidence: 97%
See 1 more Smart Citation
“…The composite prepared via CFAM showed an improvement in bulk density as it reduced the size of pores and hence porosity. Rodelas and Lippold 72 noticed that the advancing side which is more turbulent that the retreating side exhibited higher value of hardness of both higher and lower parametric conditions. A peculiar behaviour was observed on the sample prepared via low heat input parametric combination.…”
Section: Friction Stir Additive Manufacturingmentioning
confidence: 97%
“…Rodelas and Lippold 72 observed that the samples manufactured using higher heat input parametric combinations ensued better material mixing and distribution of material in the advancing side of the nugget zone. This behaviour was mainly attributed to the high strain rate and high local thermal gradient on the advancing side of the tool.…”
Section: Friction Stir Additive Manufacturingmentioning
confidence: 99%
“…Grain refinement during FSP was discovered to be caused by a continuous dynamic recrystallization process [72]. The authors called the process of adding other substances into the substrate processed via FSP as Additive Friction Stir Processing (AFSP), as previous works [73,74] applied the additive technique to FSP to locally change the composition and constituent phases. [79] used the FSP method to develop a higher volume percentage of CNTs reinforced composite.…”
Section: Tungsten Carbidementioning
confidence: 99%
“…based on the methods incorporated like friction welding-based AM, friction deposition-based AM, and friction stir welding-based AM. Linear friction welding (LFW), 27 rotary friction welding (RFW), 28 friction surfacing (FS), 29 friction deposition (FD), 30 friction assisted seam welding (FASW), 31 additive friction stir (AFS), 32 and friction stir additive manufacturing (FSAM) 33 are the different types of FATs commonly used. All the above techniques are variations of friction welding.…”
Section: Introductionmentioning
confidence: 99%